Analysis of 4G Wireless Technology: Worldwide Wireless Web (wwww) - Naganjaneyulu, Dr. K. V; Siddiqui, Mohammed Ahsan; E, Sai Alekhya; K, Akshara (IJRDO -Journal of Computer Science Engineering, 2015)
In today’s era wireless services are the most preferredand dominating means of services of the world. Therapid increase in the service is due to theadvancement of technology, especially the wirelesstechnology. The worldwide revolution in mobile andinternet technology have changed our way of livinglife. 4G will be the fourth generation of wirelessnetworks, which is expected to dominate the currentgenerations in the coming decades. In today’stechnology of mobile networks and wireless systemsmost users are using 3G, which is the 3rd generationof mobile networks and almost every single user isenjoying this wonderful wireless technology. But atrue confess is that most users are already waiting forthe next generation of mobile networks, which iscalled 4G. This paper gathers and reviews theemerging 4G wireless technology which is coined asWorldwideWireless Web (wwww)